Perancangan Desain Vas Bunga Berbahan Kaca Patri - Muthia Maira; Maharani D.P.,Ph.D. (Penerbit Itenas, 2024)
This research focuses on the design of flower vases aimed at young couples, career women, home decor enthusiasts, and flower arrangement lovers, utilizing stained glass as the primary material. The study adopts the Design Thinking method as an in-depth framework to understand the needs and preferences of the target market, as well as opportunities for developing stained glass as a home decor commodity. In this context, the design of flower vases goes beyond mere functionality, delving into the potential for creativity and aesthetics to meet consumer expectations. The Design Thinking method is used to identify challenges and opportunities within the industry, gather consumer insights, and formulate innovative solutions.The outcome of this research is a series of flower vases that combine the artistic touch of stained glass. These products serve as beautiful flower containers and make a statement of art that enriches interior spaces. Keywords: flower vases, home decor, stained glass